舌筋体内に発生し舌背に瘻孔を形成した類皮囊胞の1例 - 森田, あづさ; 土谷, 麻衣子; 柴田, 真里; 泉, 祐幸; 山口, 聰 (日本口腔外科学会雑誌, 2019)
Dermoid cysts of the tongue are rare. We present a case of dermoid cyst in the tongue muscle. An 18-year-old woman was referred to our department because of bleeding of the tongue. A small mass had been present since birth, but was never diagnosed. The mass was present in the tongue muscle and had formed a fistula on the dorsal surface of the tongue. Previous reports indicated that dermoid cysts of the tongue were smaller and occurred in patients at younger ages as compared with those found at other sites. The patient showed no evidence of recurrence 2 years postoperatively.